Developing Play Therapy Packcage (Toddler, Preschool, School Age) in Hospitalized Children of Pasca Acute Phase in Semarang - Nurhidajah Nurhidajah; Lucia Endang Hartati; Titin Suheri (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
Is a condition which causes emotional distress for children. In hospital, play is belived as a method to ventilate anxiety so that the children may away from the stressor. Therapeutic play provides structured and constructive play that sinergy with child condition so that facilitate healing. This study aims to analise the difference of knowledge and skill level of nurses before and after training of development of play therapy package. This study was conducted in three hospitals including RS Pantiwilasa Citarum, RS Tugurejo semarang, and RSU Kota Semrang. The population were all pediatric nursing in three hospitals of 40. Purposive sampling was applied to achieve 30 respondents. One group pre test-post test design was used as research design. The Questioner of Knowledge and Skill of development of play therapy package was used to collect the data. This study showed that there was difference of knowledge level before and after the training conducted (z=4.155; p=0.000) and there was difference of skill before and after the training conducted (z=4.812; p=0.000). The seven package results were bottle bowling, straw blow painting, sailboat blowing, buble printing, magic bottle, ballon rocket dan fishing game. This study recommends that it is important to apply this play therapy package during children hospitalisation.